PENGARUH TEKNIK GUIDED IMAGERY TERHADAP TINGKATKECEMASAN PASIEN PRA OPERASI SECTIO CAESAREA DI RUANG SRIWIJAYA RSUD. Prof. Dr. SOEKANDAR KABUPATEN MOJOKERTO - YUSWO YANI, LASIYATI; Yuni Kurniawati, Farah (JURNAL KEPERAWATAN BINA SEHAT, 2017)
Sectio caesarea surgery is an action that can cause tension (stress). Mothers who will undergo surgery sectio caesarea generally experience anxiety (ansietas) that vary from mild to severe levels. Guided imagery is a therapeutic technique used for relaxation and can reducing anxiety. This study aims to prove the influence of guided imagery techniques on changes in anxiety levels of preoperative patients sectio caesarea in RSUD. Prof. Dr. Soekandar Mojokerto regency. In this research the design used is pre experiment with one-group type pre-post test design. A sample of 15 people was taken by accidental sampling. Given guided imagery therapy at 2 hours before surgery then performed tabulation of data tested using descriptive analysis mode. Data collection using HARS questionnaires. There is influence of guided imagery technique to change anxiety level of pre surgical patient of sectio caesarea which level of anxiety before given guided imagery technique obtained data more than half that is 9 respondents (60%) with moderate anxiety level and anxiety level after given guided imagery technique obtained data more than half that is 9 respondents (60%) with mild anxiety level. Guided imagery technique capable of making the visual cortex of the brain processing the imagination strongly associated with the autonomic nervous system that controls involuntary movements include: pulse, respiration and physical response to stress. Guided imagery can also secrete endorphin hormones that can help the relaxation process to affect of anxiety levels.Keywords: Anxiety, Sectio Caesarea, Guided Imagery.